Development of Ecological Patent in Southeast Asian Countries: Linkages between Economic Growth, Environment and Innovation - Wiyendi, Guido; Suyanto, Suyanto; Kartikasari, Cynthia Yohanna (International Journal of Energy Economics and Policy, 2024)
This study examines the impacts of gross domestic product (GDP), carbon emission, and renewable energy consumption on ecological innovation patent of five countries in Southeast Asian region, namely Indonesia, the Philipines, Singapore, Thailand, and Malaysia, for the period 2000-2019. Two methods are applied; those are Ordinary Least Squared (OLS) and Generalized Least Squared (GLS). The results show that GDP provides a positive and significant impact on ecological innovation patent in the five countries. Similarly, carbon emission leads the ecological innovation patent. The same finding prevails in the impact of renewable energy consumption, in which it leads to further ecological innovation. The implication of this study is on the urgency for policies toward ecological innovation patent in reducing environmental damage in Southeast Asian countries.